The influence of obesity and insulin resistance on the progress of bronchial asthma - G. V. Yeryomenko (Zaporožskij Medicinskij Žurnal)
Objective – to evaluate the clinical and laboratory parameters in patients with bronchial asthma and obesity based on the distribution of adipose tissue